Hierarchical and Nonlinear Dynamics in Prefrontal Cortex Regulate the Precision of Perceptual Beliefs - Gollo, Leonardo L.; Karim, Muhsin; Harris, Justin A.; Morley, John W.; Breakspear, Michael (Frontiers in Neural Circuits, 2019)
Actions are shaped not only by the content of our percepts but also by our confidence in them. To study the cortical representation of perceptual precision in decision making, we acquired functional imaging data whilst participants performed two vibrotactile forced-choice discrimination tasks: a fast-slow judgement, and a same-different judgement. The first task requires a comparison of the perceived vibrotactile frequencies to decide which one is faster. However, the second task requires that the estimated difference between those frequencies is weighed against the precision of each percept – if both stimuli are very precisely perceived, then any slight difference is more likely to be identified than if the percepts are uncertain. We additionally presented either pure sinusoidal or temporally degraded “noisy” stimuli, whose frequency/period differed slightly from cycle to cycle. In this way, we were able to manipulate the perceptual precision. We report a constellation of cortical regions in rostral prefrontal cortex, dorsolateral prefrontal cortex and superior frontal gyrus associated with the perception of stimulus difference, the presence of stimulus noise and the interaction between these factors. Dynamic causal modelling (DCM) of these data suggested a nonlinear, hierarchical model, whereby activity in the rostral prefrontal cortex (evoked by the presence of stimulus noise) mutually interacts with activity in the dorsolateral prefrontal cortex (evoked by stimulus differences). This model of effective connectivity outperformed competing models with serial and parallel interactions, hence providing a unique insight into the hierarchical architecture underlying the representation and appraisal of perceptual belief and precision in the prefrontal cortex.